Implementing new technologies for complex care: The role of embeddedness factors in team learning. Issue 1 (10th June 2019) - Stevens, Merieke; van Schaik, Jan
Abstract: Bearing the rising health care costs of our aging global population is one of the most urgent challenges society is facing. We study the implementation of new medical technologies as one way to increase the effectiveness of care, particularly in the area of aortic disease—a condition that affects an increasing number of patients globally. Our research focus is the implementation of complex endovascular treatment techniques by a multidisciplinary aortic treatment group, in addition to their traditional open treatment of aortic disease. We find that relational and cognitive embeddedness factors support team learning, which in turn enables the team to achieve its self‐set goals of treating more patients; offering more tailor‐made care; and providing endovascular treatment in emergency situations. At the end of our data collection period, the first steps toward the team's ultimate goal of offering patient‐centered care were also taken. Abstract : Author Video